Sustainable use of continuous positive airway pressure in extremely preterm infants during the first week after delivery. Issue 6 (4th July 2006) - Booth, C; Premkumar, M H; Yannoulis, A; Thomson, M; Harrison, M; Edwards, A D
Abstract : Background: Early use of nasal continuous positive airway pressure (nCPAP) may reduce lung damage, but it is not clear how many extremely preterm infants can be cared for without mechanical ventilation on the first days after delivery. Objectives: To describe our experience of nCPAP in infants born at <27 weeks' gestation and to determine the chance of reintubation of this group of extremely preterm infants. Methods: A retrospective, observational study examined the period from November 2002 to October 2003, when efforts were made to extubate infants to nCPAP at the earliest opportunity. Data were collected on all infants born at <27 weeks' and gestation admitted to The Neonatal Intensive Care Unit, Queen Charlotte's and Chelsea Hospital, London, UK. The chance of an individual infant requiring reintubation within 48 h of delivery was estimated, calculating the predictive probability using a Bayesian approach, and oxygen requirements at 36 weeks' postmenstrual age were examined. Results: 60 infants, 34 inborn and 26 ex utero transfers, were admitted; 7 infants admitted 24 h after birth were excluded and 5 died within 48 h. The mean birth weight was 788 g and the gestational age was 25.3 weeks. Extubation was attempted on day 1 in 21 of 52 infants on ventilators and was successful in 14; and on day 2 in 14 of 35 and successful in 10 of infants extubated within 48 h of delivery survived to discharge. 5 of 23 infants on mechanical ventilation at 48 h of age were on air at 36 weeks postmenstrual age, and 12 of 26 of those were on nCPAP at 48 h of age. The probability of an individual baby remaining on nCPAP was 66% (95% CI 46% to 86%) on day 1 and 80% (95% CI 60% to 99%) on day 2. The smallest infant to be successfully extubated was 660 g and the youngest gestational age was 23.8 weeks. Conclusions: Extremely preterm infants can be extubated to nCPAP soon after delivery, with a reasonable probability of not requiring immediate reintubation.